KARAKTERISASI ALIRAN LAHAR DENGAN ANALISIS AMPLITUDO REAL TIME SEISMIC AMPLITUDE MEASUREMENT (RSAM) DAN SPEKTRUM SINYAL SEISMIK MIKRO DI TIGA STASIUN PENGAMATAN GUNUNG MERAPI - , PAULA ASCARYANI EFFRIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study of the distribution values of Real Time Seismic Amplitude Measurement, seismogram time series and frequency spectrum from Micro tremor signal of lahars has been conducted in January to July 2011 at the mountainside of Merapi volcano. The activities of Merapi produce the high level of materialâs concentration. 140millions m3 of the eruptionsâ materials have been deposited around Merapi, and because of the high level of rainfalls, lahar hazard would be triggered. This study has been done in the 3 monitoring stations of Sungai Boyong, by names SBY1, SBY2 and near to Sungai Gendol by name GDN1. Data was collected using 1 component seismometers with a sampling rate 100 ms and a frequency of 1Hz. The first data is statistic values of RSAM and seismic data which have .seisan format that used to be converted to .sac format and processed by software Swarm and Geopsy for analyzing seismogramâs pattern and the frequency of its spectrum. These distribution values can show the characteristic of lahars. The results of data processing showed that the RSAM amplitudes have values by interval 1.000-10.500 for 6 events of lahars and 1.075-16.235 counts for their seismogramâs amplitude by at least 1 hour of each durations. The average frequency of the stream flows is 2.51 Hz with average amplitude 270 counts. There are 3 characteristics of lahars related to the frequency spectrum. Debris flow with frequency and amplitude : 15-16 Hz and 9.035-16.235 counts at GDN1, 11-12 Hz and 2.001-4.943 counts at SBY2, 7-10 Hz and 1.925-11.519 counts at SBY1. Hyperconcentrated flow with frequency and amplitude : 15-20 Hz and 2.797-3.616 counts at GDN1, 15 Hz and 6.690 counts at SBY1, 12-15 Hz and 1.075-1.864 counts at SBY2. The increasing of amplitude value show the increasing of materialâs concentration. The decreasing of amplitude value is related to the atenuation caused by the last frozen deposition. The increasing of frequency value happens by the increasing of fluid volumes. The large concentration of fluids would give the space motion for particles and gain the collisions.